2020
DOI: 10.1021/acsami.0c10372
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arene-Based Switched Supramolecular Photosensitizer for Self-Amplified and pH-Activated Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) has emerged as a promising and spatiotemporally controllable cancer treatment modality. However, serious skin photosensitization during the PDT process limits the clinical application of PDT. Thus, the construction of “smart” and multifunctional photosensitizers has attracted substantial interest. Herein, we develop a mitochondria-targeting and pH-switched hybrid supramolecular photosensitizer by the host–guest interaction. The PDT efficacy of supramolecular photosensitizers can be q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…To obtain an acid-triggering antibacterial photosensitizer, a porphyrin derivative with four quaternary ammonium groups (TPyP) was first synthesized according to the previous report. 16 The detailed synthetic processes are presented in Scheme S1 (ESI†) and the 1 H NMR spectrum confirmed that TPyP was successfully synthesized (Fig. S1, ESI†).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…To obtain an acid-triggering antibacterial photosensitizer, a porphyrin derivative with four quaternary ammonium groups (TPyP) was first synthesized according to the previous report. 16 The detailed synthetic processes are presented in Scheme S1 (ESI†) and the 1 H NMR spectrum confirmed that TPyP was successfully synthesized (Fig. S1, ESI†).…”
mentioning
confidence: 71%
“…For the assembled process, there are two main interactions (host–guest and electrostatic interaction) between AgTPyP with four quaternary ammonium groups and pillar[5]arene (P[5]) with ten negative carboxylic acid groups to eventually drive the formation of nanoparticles with a diameter of around 212 nm. 16 Additionally, the acid-triggered feature of AgTPyP@P[5] was characterized by ζ-potential measurements in Fig. 1d.…”
mentioning
confidence: 99%
“…As is well known, mitochondrial dysfunction results in the decrease in mitochondrial membrane potential, leading to the transformation of the aggregation of JC‐1 (red fluorescence) into monomers (green fluorescence). [ 44,45 ] As displayed in Figure 1E and Figure S13, Supporting Information, compared with that of the control group (Control), the weaker green fluorescence and brighter red fluorescence were found in 4T1 cells cultured by TM, while a contrary phenomenon was displayed in cells cultured by Carbonyl cyanide 3‐chlorophenylhydrazone (CCCP) or DOX, showing brighter green fluorescence and weaker red fluorescence. The fluorescence intensity presented a conspicuous difference between TM and DOX cultured cells (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…The Q-band absorption at around 650 nm is also used in some reports. [69][70][71][72][73] However, the poor light absorption capability at this wavelength will inevitably weaken the PDT efficiency. Our cationic porphyrin TMPipEOPP (Scheme S1, ESI †) can specifically bind to the DNA G-quadruplex (e.g., KRAS), resulting in the redshift of the Soret band from 421 nm to 454 nm, accompanied by the emergence of a strong light absorption at around 692 nm.…”
Section: Characterization Of Dna-ncpsmentioning
confidence: 99%